A142 ENDOSCOPIST EDUCATIONAL INTERVENTIONS ARE ASSOCIATED WITH IMPROVEMENTS IN ADENOMA DETECTION RATE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (26th February 2020) - González Moreno, E; Bishay, K; Calo, N; Scaffidi, M A; Grover, S C; Forbes, N
Abstract: Background: Screening-related colonoscopy reduces the overall morbidity and mortality associated with colorectal cancer. In order for screening-related colonoscopy to be effective and safe, endoscopists must be well trained. However, a significant degree of variation exists between endoscopists in terms of adenoma detection rate (ADR) and cecal intubation rate (CIR). ADR in particular is an important colonoscopy quality metric that has been directly and inversely related to the rate of post colonoscopy colorectal cancer (PCCRC). Educational interventions aimed at endoscopists have been developed in an attempt to optimize the performance of colonoscopy. It is unknown what benefit these have on colonoscopy quality indicators or outcomes, if any. Aims: We performed a systematic review and meta-analysis to determine whether there is an association between educational interventions aimed at endoscopists and improvements in colonoscopy quality indicators or outcomes. Methods: An electronic search was conducted through August 2019 for studies reporting on targeted endoscopist educational interventions and associations with ADR or other colonoscopy quality indicators, or outcomes. Interventions such as hands-on training modules, skills enhancement courses were included Pooled rate ratios (RR) and weighted mean differences (WMD) were calculated using DerSimonian and Laird random effects models. A priori subgroup and sensitivity analyses were performed to assess for potential methodological or clinical factors associated with any of the outcomes of interest. Results: From 2, 253 initial studies, 14 were included in the systematic review, and 8 were included in the meta-analysis for ADR, representing 76, 373 colonoscopies. Educational interventions were associated with improvements in ADR (RR 1.28, 95% confidence intervals, CI, 1.19–1.38). Educational interventions were also associated with improvements in overall polyp detection rate, PDR (RR 1.17, 95% confidence intervals, CI, 1.02–1.35). Educational interventions were not associated with longer withdrawal times (WMD -0.03 minutes, 95% CI, -0.57 - 0.51) or improved CIR (RR 1.00, 95% CI, 0.99 to 1.02), though unadjusted CIR was high in both the pre- and post-intervention groups, at 94.5% and 95.0%, respectively. Figure 1 shows Forest plots comparing pre-intervention and post-intervention rates for A) ADR, b) PDR and c) CIR. Conclusions: Our study provides evidence that educational interventions aimed at endoscopists significantly improve ADR and overall PDR. Educational interventions did not impact withdrawal time or cecal intubation rates, and thus, the specific mechanisms for their benefit remain incompletely clear. As part of quality improvement programs to optimize colonoscopy performance, educational interventions should be considered. Funding Agencies: None